Research advances on circulating long noncoding RNAs as biomarkers of cardiovascular diseases. (15th April 2022) - Cao, Mingyi; Luo, Huishan; Li, Danning; Wang, Shengjie; Xuan, Lina; Sun, Lihua
Abstract: Cardiovascular diseases (CVD) such as myocardial ischemia, myocardial infarction, heart failure, atherosclerosis, hypertension, arrhythmia, and their complications diseases are associated with increased morbidity and mortality, it is necessary to develop new diagnostic markers for CVD. LncRNAs have become a new class of biomarkers in CVD with good development prospects. Numerous studies have confirmed lncRNAs feasibility as diagnostic, prognostic and predictive tools for different types of CVD. In this review, we summarized the available knowledge regarding the clinical application value and pathophysiological mechanism of circulating lncRNA as potential biomarkers of cardiovascular disease. We reviewed the scope of application and changes of circulating lncRNAs such as ZFAS1, CDR1AS, CHAST, UCA1, HOTAIR, MIAT, NEAT1, LIPCAR, H19, NRF, NRON, MHRT, PVT1, Heat2, CASC7, GAS5, MALAT1, APPAT, HIF1A-AS1, KCNQ1OT1, NEXN in different kinds of CVD and discussed their clinical application potential as biomarker, which can help us better understand the mechanism of CVD. Highlights: Cardiovascular diseases have increased morbidity and mortality, it is necessary to develop new diagnostic markers for CVD. Accurate early diagnosis of CVD has important clinical significance. LncRNAs have become a new class of biomarkers in CVD with good development prospects. The combined application of lncRNA with miRNA may bring a breakthrough to the diagnosis and prognosis of MI.